Optimization of Photovoltaic Power Systems Modelization, Simulation and Control - Rekioua, Djamila; Matagne, Ernest; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Photovoltaic generation is one of the cleanest forms of energy conversion available. One of the advantages offered by solar energy is its potential to provide sustainable electricity in areas not served by the conventional power grid.  Optimisation of Photovoltaic Power Systems details explicit modelling, control and optimisation of the most popular stand-alone applications such as pumping, power supply, and desalination. Each section is concluded by an example using the  MATLAB® and Simulink® packages to help the reader understand and evaluate the performance of different photovoltaic systems. Optimisation of Photovoltaic Power Systems provides engineers, graduate and postgraduate students with the means to understand, assess and develop their own photovoltaic systems. As such, it is an essential tool for all those wishing to specialise in stand-alone photovoltaic systems. Optimisation of Photovoltaic Power Systems aims to enable all researchers in the field of electrical engineering to thoroughly understand the concepts of photovoltaic systems; find solutions to their problems; and choose the appropriate mathematical model for optimising photovoltaic energy.
Photovaltaic Applications Overview -- Modeling of Solar Irradiance and Cells -- Power Electronic Modeling -- Optimized Use of PV Arrays -- Modeling of Storage Systems -- Photovoltaic Pumping Systems -- Hybrid Photovoltaic Systems.
Keywords: Renewable energy resources; Electronic circuits; Power electronics; Energy systems; Renewable and Green Energy; Circuits and Systems; Power Electronics, Electrical Machines and Networks; Energy Systems